Taming the chimera of hybrid work: a work design perspective on supervisors’ working characteristics and leadership demands in hybrid work settings - Stempel, Christiane R.; Dettmers, Jan (Frontiers in Psychology, 2025)
IntroductionHybrid work models have become increasingly common, changing supervisors’ own work characteristics and their leadership demands. Based on work design research, we aim to assess hybrid work characteristics of supervisors and the job demands associated with leadership in hybrid settings.MethodsWe conducted 33 expert interviews with direct supervisors who work in hybrid work models. We asked them about their work characteristics and leadership demands, using content analysis to identify key deductive and inductive themes.ResultsRegarding supervisors’ work characteristics, findings show that specific work characteristics like information management or extended availability are perceived as typical of hybrid work. Furthermore, organizational factors and technical prerequisites play a major role in the supervisors’ working conditions and their leadership. In terms of leadership demands, it became evident that work design is especially important in hybrid settings due to reduced possibilities for direct interactions. Beyond, the quality of direct leadership interactions in hybrid environments is perceived demanding when decoding communication or perceiving problems among employees. With respect to role modeling as a leadership demand, three topics emerged when supervisors reflected on their role in hybrid work: Issues of trust and control, establishing quality social relationships, and questions around self and staff care.DiscussionOur study contributes to a comprehensive assessment of work characteristics and specific leadership demands in hybrid settings and provides new insights for the theoretical discussion on work design. In practice, the results highlight the need to analyze and adequately design hybrid work characteristics for supervisors to enable them to perform their leadership tasks.